Tomato secondary metabolites as natural regulators of Bemisia tabaci behavior and performance: current applicability and prospects - Maldonado Machado da Cruz, Victor Hugo; Rutz da Silva, Thiago; Gimenez Cremonez, Paulo; Biscaia Ribeiro da Silva, André Luiz; Vergilio Visentainer, Jesui; Rodrigues, Camila (Frontiers in Plant Science, 2026)
The sweetpotato whitefly (Bemisia tabaci) is one of the most damaging insect pests of tomato (Solanum lycopersicum), often causing severe yield losses and transmitting viral pathogens such as Tomato Yellow Leaf Curl Virus. Although chemical insecticides are commonly used for whitefly management, the rapid development of insecticide resistance in B. tabaci poses a major challenge to sustainable control. In contrast, wild tomato genotypes exhibit superior resistance, primarily attributed to the production of secondary metabolites (SMs), such as terpenoids, phenolic compounds, and acylsugars. These natural compounds affect whitefly behavior, feeding, development, and survival through both deterrent (antixenosis) and toxic or growth-inhibiting (antibiosis) mechanisms. This review investigates the roles of terpenes, phenolic compounds, nitrogen-containing SMs, and acylsugars in tomato resistance to B. tabaci, with a particular emphasis on their antixenosis and antibiosis effects. It also highlights recent advances in the characterization and application of these compounds to support sustainable whitefly management and guide resistance breeding strategies. A better understanding of the synergistic effects among metabolite classes and their integration with other control strategies could enable the development of tomato genotypes with enhanced and durable resistance to B. tabaci.